2017
DOI: 10.1002/jbm.b.34018
|View full text |Cite
|
Sign up to set email alerts
|

Repair of a critical‐size segmental rabbit femur defect using bioglass‐β‐TCP monoblock, a vascularized periosteal flap and BMP‐2

Abstract: Various synthetic bone substitutes are not suitable for reconstructing critical-size bone defects. This study tested whether a bioglass-β-tricalcium phosphate (β-TCP) monoblock is effective for repairing critical-size segmental bone defects if combined with a vascularized periosteal flap and bone morphogenetic protein (BMP)-2. A femoral osteotomy with a gap size of 20 mm was created and stabilized using a plate in 40 rabbits.The defect was left untreated (group A) or repaired using a monoblock (group B), a mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
(67 reference statements)
0
13
0
Order By: Relevance
“…Biocompatible and biodegradable synthetic polymers, such as polylactic acid (PLA), polyglycolic acid (PGA), poly(D, L-lactide-co-glycolide) (PLGA), polyethylene glycol (PEG), poly-E-caprolactone (PCL), and polypropylene fumarate (PPF), as well as their block polymers have been evaluated as potential BMP carriers to overcome the disadvantages of natural polymers, including immunogenicity and disease transmission risk [39][40][41][42]. They are also moldable into highly porous three-dimensional scaffolds, linearly oriented scaffolds, fibers, sheets, blocks, or microspheres [26].…”
Section: Bone Regeneration By Bone Morphogenetic Protein Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Biocompatible and biodegradable synthetic polymers, such as polylactic acid (PLA), polyglycolic acid (PGA), poly(D, L-lactide-co-glycolide) (PLGA), polyethylene glycol (PEG), poly-E-caprolactone (PCL), and polypropylene fumarate (PPF), as well as their block polymers have been evaluated as potential BMP carriers to overcome the disadvantages of natural polymers, including immunogenicity and disease transmission risk [39][40][41][42]. They are also moldable into highly porous three-dimensional scaffolds, linearly oriented scaffolds, fibers, sheets, blocks, or microspheres [26].…”
Section: Bone Regeneration By Bone Morphogenetic Protein Devicesmentioning
confidence: 99%
“…Inorganic materials as potential BMP carriers include calcium phosphate (CaP) ceramics, calcium phosphate and calcium sulfate cement, and bioglass [2,5,29,32,38,42,. The most commonly used inorganic preclinical materials are CaP ceramics, further subdivided into hydroxyapatite (HA), tricalcium phosphate (TCP), and biphasic calcium phosphate (BCP) containing both HA and TCP at various ratios.…”
Section: Bone Regeneration By Bone Morphogenetic Protein Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Acquiring the tissue requires additional surgical procedures and creates significant donor site morbidities, accompanied by, for example, reduced function of the donor site, additional scarring, and increased pain for the patient (Betz, 2002). A recent study in rabbits showed how the use of a vascularized periosteal flap in combination with a bioglass-β-TCP monoblock and BMP-2 supplementation was effective in repairing a large femoral defect (Pan et al, 2018), emphasizing that indeed prevascularization strategies are effective in preclinical models of critical size defects.…”
Section: Importance To Patients Post-implantationmentioning
confidence: 99%
“…Therefore, various scaffolds have been developed to overcome these limitations. At present, a large proportion of the scaffolds designed to address the reconstruction of segmental bone defects are composed of synthetic materials (e.g., ceramics, alloys, and polymers), which incorporate proteins (e.g., bone morphogenetic proteins, vascular endothelial growth factor, and stromal cell‐derived factor‐1α) and/or cells (e.g., mesenchymal stem cells and adipose‐derived stem cells) because the synthetic scaffold materials alone are inadequate to facilitate the reconstruction of critical‐sized bone defects 8‐24 . However, the use of either proteins or cells is accompanied by a higher cost and an increased likelihood of adverse effects, stemming from difficulties in controlling proteins and cells.…”
Section: Introductionmentioning
confidence: 99%